Uma proposta de otimização na conversão de energia solar em energia elétrica por painéis fotovoltaicos - Nardoto, Adriano Fazolo (2016)
Growth in Energy demand observed in recent decades has been a stimulus for the use of new energy sources, previously considered expensive. It is known that the amount of solar energy incident at Earth`s surface is enough to supply the world`s energy demand, however equipment that convert solar radiation in any kind of useful energy have low efficiency. Based from this perspective, this master's thesis aims to get a bigger extraction of electric power from a photovoltaic panel using electronic circuits that track the maximum power point of operation of the cell. This proposal was implemented experimentally as an electronic circuit attached to a photovoltaic panel. This circuit is controlled through a search algorithm to maximum power point (MPPT - Maximum Power Point Tracking) with variable step. Also, it was developed a microcontrolled management system that collects photovoltaic parameters of the panel to allow the analysis of the results. The response time and efficiency of the system were measured, obtaining situations where power gain is greater than 100 % and circuit response times ranging from 0.88 to 11 seconds.